Penggunaan Permainan Rangking Satu Dalam Pembelajaran Bahasa Arab di Pondok Pesantren Daarul Huda Li Tahfidzi al-Quran Gondanglegi - Yolanda, Refiyana; Muassomah; Radhiani, Sri Mulya (Universitas Negeri Jakarta, 2024)
Learning through games is an activity that can enhance students' inclination to engage their interests and motivation, thereby fostering a conducive learning environment. One form of game applicable in nahwu learning is the first-rank game. Implemented at Daarul Huda Li Tahfidzi Al-Quran Islamic Boarding School, this game serves as a tool for learning nahwu (Arabic syntax). This study employs descriptive qualitative research to describe the process of nahwu learning utilizing the first-rank game, along with its advantages and disadvantages in implementation. The research involves one Arabic teacher and 15 students as subjects. Data collection includes observing the nahwu learning process and conducting interviews with the Arabic teacher and twelfth-grade MA students to understand Arabic language learning. Documentation comprises the outcomes of Arabic language learning through the first-rank game. Data analysis follows the Miles and Huberman model, encompassing three stages: data reduction, data presentation, and conclusion drawing. The study reveals four stages in the nahwu learning process using the first-rank game, namely introduction, opening of learning, game preparation, game application, and closing of the learning process. Furthermore, nahwu learning packaged through this game creates an enjoyable learning atmosphere, cultivates critical thinking skills, and aids students in coordinating motor skills.